Experiences of University Students on Distance Education During the Pandemic: A Phenomenological Research - Nurtaç ÜSTÜNDAĞ-KOCAKUŞAK (Hayef: Journal of Education)
With the COVID-19 pandemic affecting the whole world, almost every country had to close educational institutions at various levels and has compulsorily switched to distance education. In this process, some countries and schools were caught unprepared for distance education, while others with advanced infrastructure and technological facilities adapted more easily. This sudden shift in the education process and the ongoing advancement of internet technologies have impacted and altered the design and implementation of distance education curricula, influencing students’ experiences and perceptions of distance education. Students’ perceptions and experiences are considered crucial elements affecting the efficiency of distance education. This study aims to describe how university students experienced the distance education process during the COVID-19 period, using a phenomenological design to structure the research. The study group consists of 12 undergraduate students from 4 different faculties of a university, selected using maximum variation and criterion sampling methods. Data were collected through a semi-structured interview form in the spring semester of the 2021–2022 academic year and analyzed through phenomenological analysis. As a result of the research, it was observed that although the participants’ experiences with distance education during the pandemic included some positive individual and educational aspects, they encountered various difficulties in technical features, course structure and processing, instructor and student characteristics, and individual and family dimensions. It was also concluded that the participants’ experiences with distance education during the pandemic were affected by several individual and educational factors, leading to changes in their daily academic lives. The study identified areas for improvement in distance education, particularly concerning exams and course management, and offered several suggestions for enhancement.